Problem Pengaturan Upaya Paksa Penangkapan Terhadap Pelaku Tindak Pidana Narkotika - Kholilur Rahman (Jurnal Hukum IUS QUIA IUSTUM, 2020)
One of the highlights in Law Number 35 of 2009 on Narcotics, is that there are 2 institutions authorized to carry out investigations, namely the National Narcotics Agency (BNN) and the Indonesian National Police. BNN investigators in the authority to attempted forced arrest using the legal basis of Article 76 of Law no. 35 of 2009 on Narcotics, while the Police investigators use Article 19 paragraph (1) of the Criminal Procedure Code. Police investigators are only authorized to make arrests with a period of 1 x 24 hours, not 6 (six) days as the authority of BNN investigators. This difference in arrangement certainly creates legal uncertainty. This research will discuss, first, the implications of the difference in the regulation of the authority for forced arrest by BNN investigators and the National Police for narcotics offenders. Second, the harmonization of arrangements for the forced arrest of narcotics offenders by BNN investigators and the National Police. The research method used is normative, using a statutory approach and a conceptual approach. The results of the study conclude that first, the difference in the regulation of the authority for forced arrest between BNN investigators and the National Police has resulted in different interpretations in its implementation, resulting in legal uncertainty and violations of the principle of equality before the law against narcotics offenders. Second, the disharmony of regulating the forced arrest of narcotics offenders by BNN and Police investigators needs to be harmonized based on the Criminal Procedure Code outlined in the integrated criminal justice system.